2021
DOI: 10.2340/16501977-2821
|View full text |Cite
|
Sign up to set email alerts
|

Evidence needs, training demands, and opportunities for knowledge translation in social security and insurance medicine: A European survey

Abstract: Objective To perform a European survey of the evidence needs and training demands of insurance medicine professionals related to professional tasks and evidence-based practice. Design International survey. Subjects Professionals working in insurance medicine. Methods Experts designed an online questionnaire including 26 questions related to 4 themes: evidence needs; training demands; evidence-seeking behaviour; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…The results indicated that adequate feedback provision would be an important behavior change technique for this target population. A relevant theory (57) was identified, offering an explanation for findings in earlier studies that physicians who were educated in the use of guidelines or other evidence sources, still found it hard to consistently use these in practice [e.g., (16,20,58)]. For example, when physicians take efforts to deliver high quality evidence based disability evaluations, but do not receive any positive feedback from their supervisor or the organization, internal mechanisms will influence their motivation and decrease their intentions to take these efforts again.…”
Section: Physiciansmentioning
confidence: 99%
See 2 more Smart Citations
“…The results indicated that adequate feedback provision would be an important behavior change technique for this target population. A relevant theory (57) was identified, offering an explanation for findings in earlier studies that physicians who were educated in the use of guidelines or other evidence sources, still found it hard to consistently use these in practice [e.g., (16,20,58)]. For example, when physicians take efforts to deliver high quality evidence based disability evaluations, but do not receive any positive feedback from their supervisor or the organization, internal mechanisms will influence their motivation and decrease their intentions to take these efforts again.…”
Section: Physiciansmentioning
confidence: 99%
“…Although physicians need to make evidence-based considerations [e.g., (49,69)] and although they received EBM training (13,19), EBM usage remains limited [e.g., (16,58)]. They still consider EBM usage difficult (20,58) and are in need of EBM assistance (2,17,18).…”
Section: Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…Translating such knowledge can be facilitated when the accessible evidence is high quality, understandable and appropriately disseminated to relevant stakeholder groups [9,10]. Ideally, end-users' evidence needs are already known before any knowledge translation activity begins: a recent survey of social security and insurance medicine professionals in the European Union showed that synthesised evidence based on primary research, as reported in guidelines and systematic reviews, is more often needed for their work than primary study evidence alone [11].…”
Section: Introductionmentioning
confidence: 99%